Fizeram-me corpo, fiz-me heterotopia: um estudo das heterotopias corporais dos personagens queers no cinema de Pedro Almodóvar - Oliveira, Mayllon Lyggon de Sousa (2018)
It is in language that things get a meaning. In it, some verbs are impersonal and have no subject. This implies not having someone to agree with, like the verb "to do”. All verb indicates an action, an act in constitution. This is the case of this study: a process of "feature", a becoming-another, a becoming-body. The materialization of one corpus, about which to tell about the body's relations with the world and with others. This constitution will be made in four main actions: did, undoing, (re) doing and did. Such actions indicate the disruption of order, to establish estrangement, to inaugurate a new way of seeing and thinking the body. This dissertation aims to investigate practices, self-care and performativity in the body constitution of queers characters in the cinema of Pedro Almodóvar. In order to do so, it appropriates the concepts of subjectivities, practices and care of himself, performativity, body, heterotopy and, methodologically, uses a deconstructionist perspective and filmic analysis to perceive the performativity and self-practices of the characters. As a clipping and object of analysis, we selected the characters Tina and Pablo from Pedro Almodóvar's Law of Desire (1987). Such characters have polymorphous sexualities, allowing us to perceive how the processes of self-constitution occur and show perspectives of sexuality subversion. Their bodies are plastic, flexible, transgressors and indicate an agonistic quest in creating an aesthetic ethical truth about themselves. In this study, we are interested in discussing the queer body and how it constitutes a heterotopy, that is, the techniques, the cares and the practices of the self by which this body subverts the previously determined spaces and determinations of the body of the relations of power imposed through the device of sexuality inaugurating counter space. It is against the triple knowledge-power-subject that defines the device of sexuality that these subjects put themselves. This is because the queer is already an overlapping of social positions, a displacement to the margin, are boundary and deviant bodies that are not content to cross the binary divisions but live on the border. To define the queer body as a heterotopy, is to understand it by subversion of the natural order. It is to see it in the modification of the spaces and positions of the discourses of normatizing sexuality. Studying it under this configuration enables the communication to understand it, immersed in a culture, from traces of an event. It is in this body that cries, that laughs, that makes party (that is a party) that are locked relations of power and is in them that they transit, establishing resistances, if doing, being and surviving.